Studi Kualitas Sungai Ditinjau dari Kelimpahan Fitoplankton - Isnaini Fitria; Arman Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this investigation is to identify the kinds of phytoplankton that can be found in the Aek Buru River's waters and to gauge the quality of the river's water. Purposive sampling, a sampling approach that considers specific data sources, is the sampling methodology employed. At surface water depths of 0 to 1.5 meters, water samples were taken. According to the study's findings, there are 4 classes and 15 different types of phytoplankton in the diversity of species collected. The conclusion of this study is the diversity of phytoplankton obtained (Chlorophyceae, Bacillariophyceae, Cyanophyceae and Chrysophyceae). The quality of river water is classified as moderately polluted waters. Key words: Phytoplankton, Water Quality, Aek Buru River